Pharmacological modulation of MRAP2 protein on murine melatonin receptor signaling - Song, Wenqi; Li, Yanchuan; Xu, Hongtao; Zhang, Yaqun; Liu, Liu; Li, Yihao; Wang, Xinran; Du, Yueming; Chen, Yining; Lyu, Jianjun; Jin, Lingjing; Zhang, Chao; et al. (Frontiers in Endocrinology, 2025)
IntroductionMTNR1A and MTNR1B, crucial for regulating circadian rhythms and various physiological processes, have well- established biological significance. The role of MRAP2, a single transmembrane accessory protein, in modulating the pharmacological activity of melatonin receptors remains unclear.MethodsWe first examined the evolutionary profiles of melatonin receptors and MRAP2 by protein sequence alignment and synteny analysis. Bulk RNA-seq was then employed to analyze the expression distribution of these genes. Next, we performed co-immunoprecipitation and Bimolecular Fluorescence Complementation (BiFC) assays to investigate the interaction of MRAP2 with melatonin receptors. We also recruited the GloSensor luminescence assay to assess the impact of MRAP2 on the Gi signaling pathway of melatonin receptors, and conducted fixed-cell ELISA to evaluate MRAP2’s effect on melatonin receptor membrane trafficking.ResultsOur results revealed that MTNR1A was most conserved in terms of evolution, while all of these genes showed adaptive changes in amphibians and zebrafish likely due to aquatic environment. MRAP2 was found to inhibit the constitutive activity of melatonin receptors and enhance their maximal agonist potency. Additionally, MRAP2 suppressed the membrane trafficking of MTNR1A, but promoted the surface trafficking of MTNR1B.DiscussionThese findings highlighted the complex regulatory role of MRAP2, and shed light on its diverse functions in GPCR biology and its potential implications in regulating physiological processes governed by melatonin signaling.